Geographical and environmental gradients shape phenotypic trait variation and genetic structure in Populus trichocarpa. Issue 4 (25th November 2013) - McKown, Athena D.; Guy, Robert D.; Klápště, Jaroslav; Geraldes, Armando; Friedmann, Michael; Cronk, Quentin C. B.; El‐Kassaby, Yousry A.; Mansfield, Shawn D.; Douglas, Carl J.
Summary: Populus trichocarpa is widespread across western North America spanning extensive variation in photoperiod, growing season and climate. We investigated trait variation in P. trichocarpa using over 2000 trees from a common garden at Vancouver, Canada, representing replicate plantings of 461 genotypes originating from 136 provenance localities. We measured 40 traits encompassing phenological events, biomass accumulation, growth rates, and leaf, isotope and gas exchange‐based ecophysiology traits. With replicated plantings and 29 354 single nucleotide polymorphisms (SNPs) from 3518 genes, we estimated both broad‐sense trait heritability ( H 2 ) and overall population genetic structure from principal component analysis. Populus trichocarpa had high phenotypic variation and moderate/high H 2 for many traits. H 2 ranged from 0.3 to 0.9 in phenology, 0.3 to 0.8 in biomass and 0.1 to 0.8 in ecophysiology traits. Most traits correlated strongly with latitude, maximum daylength and temperature of tree origin, but not necessarily with elevation, precipitation or heat : moisture indices. Trait H 2 values reflected trait correlation strength with geoclimate variables. The population genetic structure had one significant principal component (PC1) which correlated with daylength and showed enrichment for genes relating to circadian rhythm and photoperiod. Robust relationships between traits, population structure and geoclimate in P. trichocarpa reflect patterns which suggest that range‐wide geographical and environment gradients have shaped its genotypic and phenotypic variability.